1, 3-Dimethylol-4, 5-dihydroxyethyleneurea as a Potential Alternative Binder for Plywood. Issue 11 (1st November 2016) - Kong, M. T.; Lim, T. W.; Król, P.; Auriga, R.; Mamiński, M. ł.
Abstract : Two types of commercial 1, 3-dimethylol-4, 5-dihydroxyethyleneurea (DMDHEU) resins were used for the first time as the binders in 3-ply plywood manufacturing. The studies were aimed at the assessment of the applicability of DMDHEU as substitute for widely used urea–formaldehyde (UF) resins. Applied press platen temperature was 120°C, 140°C, and 160°C and pressing time was 300 s. The results indicate that the DMDHEU can be used as a binder for plywood. The mechanical properties: tensile shear strength, modulus of rupture (MOR), and modulus of elasticity (MOE) were determined – i.e., > 1.0, 75–90, and 11100–18000 MPa, respectively. It was found that platen temperature 120°C was sufficient for the proper cure of the binder and to obtain dry shear strength that met the requirements of EN 310 standard. Formaldehyde release was 2.8 ± 0.6 mg∙m –2 ∙h –1 which complied with standards for interior grade plywood.